A Comprehensive Analysis Of Medical Students’ Culture And Attitudes Towards E-Learning In Hong Kong (Cuestiones de Fisioterapia, 2023)
For the dual purposes of advancing medical knowledge and developing skilled healthcare workers, medical education is essential. When it comes to medical education, e-learning has proven to be an innovator due to its ability to revolutionise accessibility, efficiency, and student-teacher interactions. Understanding the practices, trends, and associations in this field is vital since the covid-19 epidemic quickened the adoption of online learning. The results indicate that the quality of the content is necessary for the success of online courses. Students were satisfied, more diligent and abler to adapt when the content was organised, interactive and suitable to their academic and professional aspirations. Individuals lost interest and confidence in e-learning when the content was out of date, too long or poorly structured. There were issues that made it hard to keep providing high-quality content such as not enough training for teachers, inconsistent instructional design and a priority on speedy digitisation without enough planning. A quantitative research approach and stratified sampling were used in the survey to guarantee representation throughout diverse academic and vocational categories and a total of 558 genuine responses were received from medical students. Investing in teacher training, engaging tools and well-planned lessons is key to long-term success. Blended learning is a complete method that combines flexibility with academic rigour. It combines established classroom teaching with high-quality online resources. This model prepares medical professionals to function well in rapid-paced professional conditions while making sure that education is useful in the long term.